1962
DOI: 10.1901/jeab.1962.5-225
|View full text |Cite
|
Sign up to set email alerts
|

DELAYED ALTERNATION IN THE PIGEON1

Abstract: SAINT ELIZABETHS HOSPITAL, WASHINGTON, D.C.Pigeons were studied in a delayed-response task requiring alternation of key pecks on two response keys. Blackouts of from 1 to 10 sec intervened between successive choices on the two keys.The following results were obtained: (1) Birds performed at well above chance accuracy on all the delays tested. Accuracy was generally lowest at 1-and 10-sec delays. (2) Overt postural orientations during the delay interval appeared to mediate accurate key-pecking behavior.(3) The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
22
0

Year Published

1967
1967
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 5 publications
2
22
0
Order By: Relevance
“…The opportunity of reinforcing orientation responses during the delay period was probably diminished by using the fixed-interval schedule during this period. Hearst's (1962) Blough (1959) studied delayed matching in pigeons and reported relatively horizontal delay gradients for some of his subjects during portions of the test sessions. However, Blough often observed stereotyped movements during the delay intervals.…”
Section: Resultsmentioning
confidence: 99%
“…The opportunity of reinforcing orientation responses during the delay period was probably diminished by using the fixed-interval schedule during this period. Hearst's (1962) Blough (1959) studied delayed matching in pigeons and reported relatively horizontal delay gradients for some of his subjects during portions of the test sessions. However, Blough often observed stereotyped movements during the delay intervals.…”
Section: Resultsmentioning
confidence: 99%
“…A second alternative is that the procedure used in the first three experiments allowed the usage of positional cues after incorrect trials but not after correct trials. This is noteworthy in that previous experiments have shown that a variety of organisms can easily learn spatial delayed alternation (e.g., Hearst, 1962;Livesay and Trender, 1966), while non-spatial delayed alternation has been learned only with great difficulty.…”
Section: Experiments Iv: Differences In Accuracy After Correct and Incmentioning
confidence: 87%
“…When the alternation problem involves spatial cues, such mediational behavior often includes postural orientation toward the appropriate response position (e.g., Hearst, 1962). Mediation in terms of behavioral chains is less plausible, however, for alternation problems employing non-spatial cues.…”
mentioning
confidence: 99%
“…The influence of precurrent responses on performance in delayed-choice procedures, such as delayed-matching-to-sample and alternation, has been reported in experiments with humans (e.g., Parsons et aI. , 1981;Torgrud & Holborn , 1989) and pigeons (e.g., Blough, 1959;Eckerman, 1970;Hearst, 1962;Jans & Catania, 1980;Shimp & Moffitt, 1977). In all the experiments in which precurrent responses were prevented, prohibited, or disrupted after conditions in which they occurred, this type of manipulation produced disruption of current responding.…”
mentioning
confidence: 79%